Methodical aspects of the analysis and assessment of risks of implementation of the investment construction projects (Journal of Economic Research & Business Administration, 2015)
Implementation of investment construction projects is a business with a high risk level and many commercial structures for the various reasons become unprofitable and are liquidated at the beginning of the activity. In many cases implementation of investment construction projects finished with a failure as which reasons such circumstances as can serve: low-quality planning, adverse circumstances, inexact or insufficient data exchange, control shortcomings over the external and internal environment of the project, an unsatisfactory control system. Application of methods of risk management allows to solve the main problems of identification of possible negative situations, an assessment of probability of their approach and size of consequences from their manifestation. However existence of many various methods of risk management complicates the performance of objectives. Because of uncertainty of questions in the field of classification of risks and degree of their influences, each company structures them in own way. In this regard it was formed extensive “field” for research of this subject.
Keywords: risk management; identification of risks; efficiency of investment projects; matrix of “Probability-Losses”